2014
DOI: 10.1002/mrm.25357
|View full text |Cite
|
Sign up to set email alerts
|

Quantified pH imaging with hyperpolarized 13C‐bicarbonate

Abstract: Hyperpolarized (13) C-bicarbonate pH mapping was shown to be sensitive in the biologically relevant pH range. The mapping of pH was applied to healthy in vivo organs and interpreted within inflammation and acute metabolic alkalosis models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 41 publications
(61 reference statements)
2
37
1
Order By: Relevance
“…The very short half‐life of the nuclear spin polarization in hyperpolarized H 13 CO 3 and 13 CO 2 means that the ratio reflects predominantly the extracellular pH46, 50 in regions that are relatively well perfused and that would have also received the hyperpolarized [1‐ 13 C]pyruvate. The absence of a decrease in extracellular pH measured here in CFA‐inflamed paws (pH 7.32 ± 0.09 versus pH 7.23 ± 0.06 in controls) is in contrast to a study by Scholz et al,41 who used hyperpolarized [ 13 C]bicarbonate to measure pH in an acute inflammation model in the rat leg (injection of concanavalin A 2 hours prior to imaging). The lower pH reported in this study (pH 7.0) may reflect the acute nature of the inflammation induced by concanavalin A, as compared with the more chronic inflammation induced by CFA, and also the later imaging time point used here.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The very short half‐life of the nuclear spin polarization in hyperpolarized H 13 CO 3 and 13 CO 2 means that the ratio reflects predominantly the extracellular pH46, 50 in regions that are relatively well perfused and that would have also received the hyperpolarized [1‐ 13 C]pyruvate. The absence of a decrease in extracellular pH measured here in CFA‐inflamed paws (pH 7.32 ± 0.09 versus pH 7.23 ± 0.06 in controls) is in contrast to a study by Scholz et al,41 who used hyperpolarized [ 13 C]bicarbonate to measure pH in an acute inflammation model in the rat leg (injection of concanavalin A 2 hours prior to imaging). The lower pH reported in this study (pH 7.0) may reflect the acute nature of the inflammation induced by concanavalin A, as compared with the more chronic inflammation induced by CFA, and also the later imaging time point used here.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous magnetic resonance spectroscopic imaging (MRSI) studies in rats injected with hyperpolarized [1‐ 13 C]pyruvate showed raised lactate‐to‐pyruvate ratios in CFA‐induced inflammation,39 which, considering the relationship observed between lactic acid and acidosis,9, 12, 13 suggested that acidosis must occur in this widely used model. The aim of this study was to determine if tissue acidosis actually does occur in regions where there was increased lactate labelling by using hyperpolarized [ 13 C]bicarbonate to measure tissue extracellular pH 40, 41…”
Section: Introductionmentioning
confidence: 99%
“…The maximum bicarbonate polarizations achieved in these studies are in the same range as those achieved through the direct polarization of Cs-bicarbonate (16% [13] and 19% [2] have been reported), and significantly higher than those achieved by the calcium-catalyzed decarboxylation of pyruvate (10% [14]), or the decarboxylation of pyruvate with excess H 2 O 2 (5% [15]). A major deficiency of all chemical reaction based polarization schemes is the additional time needed for the reaction to occur before imaging.…”
Section: Discussionsupporting
confidence: 65%
“…It is well known that the microenvironment surrounding tumors is more acidic than similar healthy tissue [1]. Inflammation has also been shown to cause a local reduction in pH [2]. Abnormal tissue stretch, similar to that occurring in lung parenchyma during ventilator-induced lung injury (VILI), has been shown to cause acidification of extracellular space independent of inflammation [3].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to hyperpolarized 13 C-labelled bicarbonate26, which has been proposed as a probe for clinical pH imaging and which currently is the most prominent among the hyperpolarized pH probes, ZA-based pH imaging offers several advantages: First, ZA has a relatively long signal lifetime with an apparent T 1 of ≈17 s at 7 T in vivo , whereas bicarbonate has a shorter apparent T 1 , which is ≈10 s in vivo at both 3 T and 9.4 T (refs 26, 27); second, ZA is highly soluble and does not need enzymatic conversion to become an active pH probe, whereas bicarbonate exhibits a relatively small equilibrium CO 2 signal (≈6% of HCO 3 − at pH 7.4) and limited solubility at physiological pH; third, ZA is localized in the extracellular space and slowly excreted through the kidneys and decomposes into endogenous substrates, whereas CO 2 through respiration and diffusion across cell membranes is not clearly restricted to the extracellular space; fourth, ZA relies on the determination of pH through the measurement of chemical shift displacements, whereas for bicarbonate pH mapping, there is a need for ratiometric analysis of signal amplitudes which is difficult at a low signal-to-noise-ratio (SNR); fifth, pH measurements using ZA does not involve any enzymes in contrast to bicarbonate pH imaging, where the enzyme concentration (that is, carbonic anhydrase) influences the speed at which pH can be measured.…”
Section: Discussionmentioning
confidence: 99%